Ideologi Damai Kaum Pesantren: Studi atas Narasi Kurikulum Pesantren Salaf - Iksan Kamil Sahri (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2018)
The world is currently suffering from the heat of terrorism with several religious background. Within Muslim communities, worries come up since particular terrorism actions lean upon Islam as the main source of inspiration. Academics question into this phenomenon, wheter Islam has a peaceful genetics. To answer this question remark, this research has been performed focusing on Islamic traditional education in Indonesia (salaf pesantren). The researcher focused on how the Islamic curriculum was created and applied in two Islamic institutions in East Java, Indonesia: i.e Pesantren Langitan and Pesantren Kedinding Lor to understand further the main ideology on these institutions. This research argues that peaceful ideology in salaf pesantren was created and applied on six religious subjects. Thye formulation appears from the intersectionality of Islamic jurisprudence (fiqh) and Islamic mysticism (tasawuf and tarekat).